Unlocking the relationship between domestic investment, environmental quality, and economic growth: Fresh insights from the USA - Gafsi, Nesrine; Bakari, Sayef (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the dynamic relationships among domestic investment, environmental quality, and economic growth in the United States from 1990 to 2022, providing insights into how these variables interact to shape sustainable development. The research employs cointegration estimation and a Vector Error Correction Model (VECM) to examine long-term and short-term relationships. Data on gross domestic product (GDP), gross fixed capital formation (domestic investment), and CO₂ emissions (environmental quality) were sourced from the World Bank and the World Resources Institute. Stationarity tests, lag selection, and diagnostic checks were conducted to ensure robust results. The long-term results reveal a positive bidirectional relationship between domestic investment and economic growth, as well as between environmental quality and economic growth. However, a negative bidirectional relationship exists between environmental quality and domestic investment. Short-term dynamics show unidirectional causality from domestic investment to economic growth, bidirectional causality between domestic investment and environmental quality, and between environmental quality and economic growth. The findings underscore the need for integrated policies that balance economic growth with environmental sustainability. Policymakers should channel investments into environmentally friendly sectors, implement incentives for responsible natural resource management, and strengthen regulations to mitigate environmental degradation. Such measures can promote inclusive and sustainable economic development while preserving environmental quality for future generations.